산전 유전자 검사 - 한유정(You Jung Han); 류현미(Hyun Mee Ryu) (Journal of genetic medicine, 2011)
Genetic testing has been generalized for the diagnosis of diseases and is an important method of research with advances in the life sciences. In particular, we should give better attention to the genetic test for a fetus. Because the fetus has no autonomy, ethical and social issues can arise. Therefore, appropriate genetic counseling is needed for parents to be informed with the characteristics, natural progress, and possible treatment of a genetic disease, prior to the prenatal genetic test. Physicians should also inform parents how a particular genetic risk factor relates with the likelihood of a disease, in order to assist the parents in making the best decision. Furthermore, the current law for prenatal genetic testing should be approached rationally. 유전자 검사는 생명과학의 발달과 더불어 질병 진단 및 연구의 중요한 수단으로 일반화되고있으나, 태아에 대한 유전자 검사는 자기결정권이 없는 태아를 대상으로 하기 때문에 또 다른 윤리적, 사회적 문제가 있을 수 있으므로 특별한 주의를 기울여야 한다. 따라서 태아 유전자 검사를 시행하기 전에 유전 상담이 충분히 이루어져서 부모에게 병의 진단, 자연경과, 가능한 치료를 이해시키며, 질환의 유전방식과 가족의 재발 위험도를 평가하고 그에 따른 가능한 선택을 제시하여 가족들이 질환에 대해 최선의 결정을 할 수 있게 도움을 주어야 한다. 뿐만 아니라 태아 유전자 검사에 대한 현행법의 합리적인 법률 개정도 뒷받침되어야 한다.